(untitled) ((Des)troços: revista de pensamento radical, 2023)
Tradução de: MAY, Todd. Is post-structuralist political theory anarchist? In: EVREN, Süreyyya; ROUSSELLE, Duane. Post-anarchism: a reader. London: Pluto, pp. 41-45, 2011.